PROSPECTS FOR THE DEVELOPMENT OF VOCATIONAL EDUCATION IN THE FIELD OF TOURISM IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
The article discusses the current state of vocational education in the country, identifies key opportunities for improvement, and presents potential strategies for enhancing the quality and relevance of tourism-focused vocational training programs. The authors provide valuable insights into the importance of aligning vocational education with the evolving demands of the tourism industry, as well as the potential benefits of investing in the skill development of the workforce for the country's tourism sector.